2009
DOI: 10.1093/mp/ssp006
|View full text |Cite
|
Sign up to set email alerts
|

RNA Polymerase V Functions in Arabidopsis Interphase Heterochromatin Organization Independently of the 24-nt siRNA-Directed DNA Methylation Pathway

Abstract: In Arabidopsis, pericentromeric repeats, retroelements, and silenced rRNA genes are assembled into heterochromatin within nuclear structures known as chromocenters. The mechanisms governing higher-order heterochromatin organization are poorly understood but 24-nt small interfering RNAs (siRNAs) are known to play key roles in heterochromatin formation. Nuclear RNA polymerase IV (Pol IV), RNA-DEPENDENT RNA POLYMERASE 2 (RDR2), and DICER-LIKE 3 (DCL3) are required for biogenesis of 24-nt siRNAs that associate wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
49
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 61 publications
6
49
0
Order By: Relevance
“…We currently do not know how the SUMOylation affects the Pol V functions of protein activity, stability, localization, partner interaction, which in turn mediate the TGS of aberrant genes. Previous reports have demonstrated that Pol V affects heterochromatin organization, which is independent of Pol IV (Douet et al, 2009;Pontes et al, 2009). Our study provides another case that Pol V functions in the regulation of gene expression, which does not rely on Pol IV.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…We currently do not know how the SUMOylation affects the Pol V functions of protein activity, stability, localization, partner interaction, which in turn mediate the TGS of aberrant genes. Previous reports have demonstrated that Pol V affects heterochromatin organization, which is independent of Pol IV (Douet et al, 2009;Pontes et al, 2009). Our study provides another case that Pol V functions in the regulation of gene expression, which does not rely on Pol IV.…”
Section: Discussionsupporting
confidence: 61%
“…Pol IV collaborating with RDR2 and DCL3 is responsible for 24-nucleotide small-interfering RNA (siRNA) biogenesis, whereas with the help of chromatin-remodeling DDR complex (DRD1, DMS3, and RDM1), Pol V functions to generate scaffold RNAs for guiding sequence-specific DNA methylation by siRNAs (Onodera et al, 2005;Pontier et al, 2005;Wierzbicki et al, 2008;Zhou and Law, 2015). Loss of Pol V or DRD1 disrupts heterochromatin organization during interphase; on the contrary, loss of Pol IV, RDR2, or DCL3 does not (Pontes et al, 2009). Approximately 60% of Pol V-occupied regions overlap with the regions of 24-nucleotide siRNA complementarity and cytosine methylation; however, about one-quarter of Pol V peaks occur at loci (mostly genes) lacking significant cytosine methylation or siRNA signatures (Wierzbicki et al, 2012), indicating that Pol V may not function only in the RdDM pathway in Arabidopsis.…”
mentioning
confidence: 99%
“…Thus, one possibility is that if we could examine siRNAs and transcription when paramutation is established, we might see a correlation between siRNAs or a larger RNA and establishment of silencing. There is precedence for a role of larger RNAs in silencing in Arabidopsis in that the heterochromatic silencing of certain 5S ribosomal DNA tandem repeats requires Pol V and most likely longer RNAs but not other RdDM components (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Pol V also mediates RdDM-independent silencing at pericentromeric repeats (Douet et al 2009;Pontes et al 2009). It was unknown how broadly Pol V is needed across the whole genome.…”
Section: Genome-wide Examination Of the Rddm Modelmentioning
confidence: 99%